New Media Consumption Process though Xiaohongshu Application for Henan Tourism Economic Promotion - Na, Gong; Yossakrai, Kanokrat; Buranadechachai, Sukanya (Journal of Dhamma for Life, 2025)
The objectives of this research were (1) To explore the situation of cultural tourism and economy of Henan province; (2) To analyze Xiaohongshu application to do consumption process for Henan tourism economic promotion; and (3) To propose guidance to develop new media consumption process though Xiaohongshu application for Henan tourism economic promotion. The research was mixed methodology research. Population was Chinese People, totalling 1,410,000,000. The sample size was determined by Taro Yamane (error 0.05), obtained by purposive sampling method, totaling 400. The 14 key informants were 4 Xiaohongshu travel bloggers, 2 travel agent staffs, 2 Communication academic, 1 tourism academic, 5 tourists using Xiaohongshu (who is interested in traveling in Henan and has traveled in Henan through Xiaohongshu). The instruments used for data collection were questionnaire, in-depth interview, and document. The statistics used for data analysis were percentage, mean, standard deviation and Multiple linear regression. The research findings revealed that; (1) Henan’s cultural and tourism industry has become an emerging pillar from helping economic problem from COVID-19 pandemic, Xiaohongshu users prefer to obtain travel information through new media platforms, with Xiaohongshu being their first choice, (2) Tourists use Xiaohongshu like to search for information about Henan tourism, and the platform attracts tourists by publishing content in various forms. Moreover, Users both passive and active behaviour all pre-tourism step, during tourism step, and post-tourism step by search for information, share experience. Therefore, Xiaohongshu is beneficial to the economic growth of cultural tourism in Henan province (3) Xiaohongshu can consider further optimizing the user interface and operation process to improve the user experience. At the same time, it can also provide more accurate and personalized information services according to the specific needs of users.